PENERAPAN MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE DALAM MATA PELAJARAN AKIDAH AKHLAK - Dedi Wahyudi; Lilis Marwiyanti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Inside circle learning model has a clear structure and structured, students can work together with peers through mutual cooperation and share information obtained during the learning process. This learning model can improve learning outcomes of learners with the support of learners in the application of learning model inside outside circle. Application of learning model inside outside circle in faith material to qada and qadar can help students understanding that faith to qada and qadar is belief in heart, comprehension which can be expressed by oral, applying by behavior and deed which shows that we believe that destiny of Allah SWT must happen and believe that the efforts we do will not be in vain. With this model students are not only easy to understand the material that the teacher will convey, but will also be able to develop creativity and activities during the learning process.